C-MPL Is a Candidate Surface Marker and Confers Self-Renewal, Quiescence, Chemotherapy Resistance, and Leukemia Initiation Potential in Leukemia Stem Cells. (5th September 2018) - Li, Huan; Zhao, Na; Li, Yihui; Xing, Haiyan; Chen, Shuying; Xu, Yingxi; Tang, Kejing; Tian, Zheng; Wang, Min; Rao, Qing; Wang, Jianxiang
Abstract : Acute myeloid leukemia (AML) is initiated and maintained by a unique, small subset of leukemia cells known as leukemia stem cells (LSCs). Self-renewal, quiescence, and chemotherapy resistance are key stemness properties of LSCs that are essential for poor clinical responses to conventional therapies. Identifying LSC surface markers and targeting LSCs are important for the development of potential therapies. In this study, application of chemotherapy treatment in AML-ETO9a (AE9a) leukemia mice led to the enrichment of a chemotherapy-resistant cell population identified as Lin − c-Kit + c-MPL + . In addition, this c-MPL-positive cell population within Lin − c-Kit + leukemia cells included a high percentage of cells in a quiescent state, enhanced colony formation ability, and increased homing efficiency. Serial transplantation demonstrated that Lin − c-Kit + c-MPL + cells displayed a significantly high potential for leukemia initiation. Furthermore, it was demonstrated that in AML patients, c-MPL was expressed on the majority of CD34 + leukemia cells and that the proportion of c-MPL + cells in CD34 + leukemia cells is associated with poor prognosis. Finally, AMM2, an inhibitor of c-MPL, was shown to significantly enhance the survival of AE9a leukemia mice when combined with chemotherapeutic agent. These results indicate that c-MPL is a candidate LSC surface marker that may serve as a therapeutic target for the elimination of LSCs. Abstract : In this study, application of chemotherapy treatment in AML-ETO9a leukemia mice led to the enrichment of a chemotherapy-resistant cell population identified as Lin-c-Kit+c-MPL+. This c-MPL-positive cell population within Lin-c-Kit+ leukemia cells included a high percentage of cells in a quiescent state, enhanced colony formation ability and high potential for leukemia initiation. The results indicate that c-MPL is a candidate leukemia stem cell (LSC) surface marker that may serve as a therapeutic target for the elimination of LSCs.